A COMPARATIVE EVALUATION OF ELECTROCARDIOGRAMS RECORDED IN CLASSICAL LIMB AND EXPERIMENTAL METHODS IN NATIVE CATS OF ODISHA, INDIA - SUBHASHREE SARANG; A. P. K. MAHAPATRA; S. MOHAPATRA; A. K. KUNDU; SUBHASHREE SARANGI; , A. P. K. MAHAPATRA; S. MOHAPATRA; A. K. KUNDU (The Bioscan, 2015)
The ECG was recorded in the leads I, II, and III by two methods of leads’ positioning: the classical limb method and the experimental method (red electrode at back of the neck, yellow electrode in the sacrum area, green electrode in the area beneath the breastbone and black electrode on the skin fold of the knee joint of the right hind limb). The heart rates were 157.69 (S.E.±5.05) and 134.54 (S.E.±3.08) in classical limb and experimental methods respectively. The mean electrical axis (MEA) shifted from 47.74 (S.E.±3.75) º in the classical limb method to 119.12 (S.E.±0.91) º in the experimental method. The amplitude of P- and R-waves was negative in lead-I only. Since, it is often very difficult to restrain the cats with the electrodes attached to all its limbs, the values obtained in the experimental method could be used as reference values for this alternative way of ECG recording in adult cats.